Komparasi Karakter Morfologi Sapi Madura Sonok dan Madura Pedaging - Siti Lutvaniyah; Dyah Perwitasari Farajallah; Achmad Farajallah (Jurnal Ilmu Pertanian Indonesia, 2017)
Madura cattle was selected into three groups by Madura people, there are karapan, sonok, and beef cattle. This selection based on morphological characters and pedigree. The differences of morphological characters in Sonok and beef cattle have not been reported. This research aimed to analyze morphological characters of both types, such as the differences in behaviors. This research was conducted from January-April 2016 at Sumenep and Pamekasan region, Madura Island. Preliminary was conducted with interviews, observation, and literature studies to obtain some characters which will be observed. Eighteen characters were observed in forty-two sonok cattle and fifty beef cattle. Qualitative data was analyzed by frequency analysis and use as input for principal component analysis (PCA) in Minitab 16 Statistical Software. The result shows that all of the observed cattle are divided into two groups. It indicates that sonok and beef cattle have different color around the eye area, the existence of back line, horn direction, and the existence of hump. However, further, observation is needed to find a robust character which can distinguish sonok and beef cattle for sonok selection.